Mitigating the dissolution of V2O5 in aqueous ZnSO4 electrolyte through Ti-doping for zinc storage - Wei, Zihe; Wang, Xuehua; Zhu, Ting; Hu, Ping; Mai, Liqiang; Zhou, Liang (Chinese chemical letters, 2024)
Aqueous zinc-ion batteries (AZIBs) have become a hotspot for electrochemical energy storage owing to the high safety, low cost, environmental friendliness, and favourable rate performance. However, the serious dissolution of cathode materials in aqueous electrolytes would lead to poor cyclability, which should be addressed before commercialization. Herein, we designed a Ti-doped V2O5 with yolk-shell microspherical structure for AZIBs. The Ti doping stabilizes the crystal structure and relieves the dissolution of V2O5 in aqueous ZnSO4 electrolyte. The optimized sample, Ti0.2V1.8O4.9, delivers a high capacity (355 mAh/g at 0.05 A/g) as well as good capacity retention (89% after 2500 cycles at 1.0 A/g). This work provides an effective strategy to mitigate the dissolution of cathode material in aqueous ZnSO4 electrolyte for cyclability enhancement. [Display omitted] Ti-doped V2O5 yolk-shell microspheres are synthesized by a spray drying method, and the optimized Ti0.2V1.8O4.9 delivers a high capacity and improved cyclability in low cost aqueous ZnSO4 electrolyte. This study provides an effective strategy to mitigate the dissolution issue of cathode material in aqueous electrolytes by transition metal doping.